Expediency heuristic in university conference webpage - Mohd Sidek, Roslina; Ahmad, Noraziah; Klaib, Mohamad Fadel Jamil; Abd Wahab, Mohd Helmy (2010)
In this paper, we present a webpage that has been developed based on heuristic elements which refer to the International Conference Software Engineering and Computer Systems for requirement. Heuristic and web base method have been applied in this system with combination of PHP language and MySQL as database system. The objective of this paper is the development of a webpage that has been developed based on heuristic elements which refer to university conference is to simplify and get quality webpage in using conference webpage for the Faculty of Computer Systems and Software Engineering, University Malaysia Pahang in Malaysia. Besides minimize human contacts thus provide fast, efficient, transparent and effective service to author, admin and reviewer. Therefore this system can facilitate user by computerized all the form accordance to paper submission, review papers, download paper, assign reviewer through heuristic online university conference webpage.